EVALUASI TERAPI ANTIDEPRESAN PADA PASIEN DENGAN GEJALA DEPRESI DI RSJD AMINO GONDOHUTOMO SEMARANG - Palupi, Poppy Diah; Novembrina, Metrikana (SEKOLAH TINGGI ILMU FARMASI YAYASAN PHARMASI SEMARANG, 2017)
ABSTRACTDepression is a unipolar mood disorder, where emotions are expressed with depressed feelings, which in extreme conditions greatly affects one's perception. The purpose of this study was to evaluate antidepressant therapy in patients with depressive symptoms at RSJD Dr. Amino Gondohutomo Semarang, Central Java, Indonesia. This study was conducted with a quantitative, non-experimental approach, and cohort design study. Data were collected by retrospective method from the medical records of depressed patients. The number of subjects was 83 patients, consisting of 3 patients with medium depression diagnosis, 7 patients with severe asymptomatic depression diagnosis, and 73 patients with severe depression diagnosis with psychotic symptoms. Using one-way anova, the length of hospitalization days between depression groups showed no significant difference (p> 0.05). So it can be said that the type of depression does not affect to the length of hospitalization days. The length of hospitalization days in severe depression group with psychotic symptoms using TCA, SSRI, and TCA-SSRI were tested using one way anova, and the results were no significantly different (p> 0.05). This result showedanti-depressant selection in patients with severe depression and psychotic symptoms does not affect to the length of hospitalization days. The result of Fisher exact test in all subjects with depression showed there was no relation between anti depressant selection on length of stay (LOS). There were no significant differences between length of stay (LOS) with type of depression and selection of antidepressant. There was no association between anti-depressant group and length of hospitalization days (LOS).